2013
DOI: 10.1007/s00268-013-2122-6
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐center Large‐volume Experience in the Surgical Management of Hydatid Disease of the Lung With and Without Extrapulmonary Involvement

Abstract: Although multiple session surgery is used to decrease the risk of complications, contamination, and infection in multiple or bilateral pulmonary hydatid cyst cases, or in patients with other organ involvement, single-session surgery can be used in selected cases taking into account the operative trauma, financial consequences, and psychological profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In the literature, it has been reported that only 10-19% of patients are asymptomatic. Most common symptoms are cough, chest pain, fever, hemoptysis, sputum production (5,6,8). The same pattern can be seen in our patients too.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the literature, it has been reported that only 10-19% of patients are asymptomatic. Most common symptoms are cough, chest pain, fever, hemoptysis, sputum production (5,6,8). The same pattern can be seen in our patients too.…”
Section: Discussionsupporting
confidence: 87%
“…Hydatid Disease (HD) most frequently involves the parenchyma of the liver (55-75%); however some of the parasites escape through the microvascular barrier and reach the lung (15-40%) (1,6). There is no specific symptom for pulmonary hydatid disease (PHD).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with larger cysts who are at a higher risk of medical therapy failure and complications are surgically treated [18][19][20][21]. There are reports advocating for surgery as the first line of management regardless of cyst volume because of the risk of complications [18,[22][23][24]. In light of our experience, surgical intervention is not necessary for cysts smaller than 5 cm, which could be successfully treated with albendazole, eliminating surgical risks and complications.…”
Section: • Dokumcu Et Al Thoracoscopy Vs Thoracotomy In the Treatmementioning
confidence: 89%